Reinventing the Adult Education Curriculum within an Urban Latino Community - Tom Hearney; Roberto Sanabria; Elizabeth Tesdell; Wendy Figueroa; Delilah Garcia; Marvin Garcia; Lourdes Lugo; Gloricelly Martinez-Franceschi; Socorro Rivera; Tito Rodriquez; Erica Van Opstal (Adult Education Research Conference, 2001)
This paper will examine an adult education Masters program developed in collaboration with an urban Latino community. Its pedagogy and its content are described in the voices of students reflecting on how they have applied their new understandings and research skills to social change initiatives within the community.